2001
DOI: 10.1111/j.1834-7819.2001.tb00284.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health Among Vietnamese Using a Community Health Centre in Richmond, Victoria

Abstract: Background: The purpose of this study was to assess the prevalence of specific oral diseases in a Vietnamese background population living in Melbourne, Australia, and to compare these findings to existing oral health data. Methods: One hundred and fifty‐eight subjects of Vietnamese background, 18 and older, participated in the study. Results: Subjects were clinically examined, in a cross‐sectional study, using standard World Health Organization criteria. The mean decayed, missing and filled surfaces scores wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 18 publications
2
24
0
2
Order By: Relevance
“…Dental disease is highly prevalent among immigrant and refugee populations in Australia 31,32 as well as other western industrialized countries 33,34 . Common oral health problems include dental caries, periodontal disease (gum disease), functional malocclusion and dentofacial trauma 31,34 . Under‐nutrition and poor nutrition both prior to and following resettlement are thought to contribute to poor dental health 35 .…”
Section: Dental Healthmentioning
confidence: 99%
“…Dental disease is highly prevalent among immigrant and refugee populations in Australia 31,32 as well as other western industrialized countries 33,34 . Common oral health problems include dental caries, periodontal disease (gum disease), functional malocclusion and dentofacial trauma 31,34 . Under‐nutrition and poor nutrition both prior to and following resettlement are thought to contribute to poor dental health 35 .…”
Section: Dental Healthmentioning
confidence: 99%
“…12,[15][16][17][18][19][20][21][22][23] Moreover, publications on transcultural dental care examine the oral health status amongst ethnic minorities, their use of oral health care services as well as their oral health beliefs, knowledge, attitudes and behaviours. [24][25][26] Studies have confirmed the impact of socio-cultural factors on the oral health of culturally diverse groups and identified difficulties, including basic language facility and the comprehension of mandatory managed care, as being amongst the major common barriers to the provision and attainment of quality dental care. 17,[27][28][29] Ensuring cultural or even linguistic matching is often not possible.…”
Section: Introductionmentioning
confidence: 99%
“…Very few immigrants have dental insurance 29,30 , but some are entitled to limited dental services in both countries if they have little income, and if they can find a dentist who accepts the relatively low fees paid for these services 31 . Melbourne, in contrast to Vancouver, has a more extensive government‐sponsored dental service through community health centres that enhance access to care for immigrant groups 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The function and appearance of the mouth and teeth are described typically in the context of hygiene, health and comfort, where comfort includes eating, acceptance of appearance and overall well‐being with natural or artificial teeth. Cleanliness and appearance of the mouth and teeth are influenced by a sense of social responsibility, which seems to increase after immigrating to the West, and is unlike other communities of older Chinese immigrants 7,10–12 . Concerns about chronic diseases of the mouth and teeth were associated with their impact on general health, especially digestion.…”
mentioning
confidence: 99%